2017
DOI: 10.1021/acsomega.6b00254
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mixed Electrolyte of N,N-Dimethylacetamide/Sulfolane and Its Application in Aprotic Lithium–Air Batteries

Abstract: Aprotic lithium–air batteries have recently drawn considerable attention due to their ultrahigh specific energy. However, the chemical and electrochemical instability of the electrolyte is one of the most critical issues that need to be overcome. To increase the stability and maintain a relatively high conductivity of the lithium ion, a mixed electrolyte of sulfolane (TMS) and N , N -dimethylacetamide (DMA) was evaluated and tested in an aprotic lithium–air battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, the electrolyte with 50% DMA has more rapid kinetics than that with 20% DMA, and the reduced density could be one of the reasons. Moreover, a previous investigation says that increasing the DMA content results in a significant decrease in viscosity. And this decrement in viscosity enhances the transportation and ionic conductivity of ionic species.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the electrolyte with 50% DMA has more rapid kinetics than that with 20% DMA, and the reduced density could be one of the reasons. Moreover, a previous investigation says that increasing the DMA content results in a significant decrease in viscosity. And this decrement in viscosity enhances the transportation and ionic conductivity of ionic species.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the scientific community has been designing the above-described solvents to give a further edge to forming different mixed electrolytes. Earlier studies showed the exclusive functioning of mixed electrolytes over single electrolytes in various aspects of the Li-O 2 device. Recently, Wang and coworkers reported a binary hybrid electrolyte for the aprotic lithium-air cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rechargeable metal–air battery has advantages such as low cost, environmental friendliness, and high safety performance; especially, zinc–air batteries are expected to be one of the most promising new energy batteries for the next generation because of their high energy density. 14 The theoretical energy density can reach as high as 1350 kW h kg –1 . 57 However, because of technical limitations, the rechargeable zinc–air batteries have not yet been commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…The rechargeable metal–air battery has advantages such as low cost, environmental friendliness, and high safety performance; especially, zinc–air batteries are expected to be one of the most promising new energy batteries for the next generation because of their high energy density. The theoretical energy density can reach as high as 1350 kW h kg –1 . However, because of technical limitations, the rechargeable zinc–air batteries have not yet been commercialized. Taking the zinc anode as an example, it is much denser and has a smaller specific surface area; dendritic or mossy growth of zinc results in the morphology and shape change during the charging/discharging process, leading to the decline in the performance and the low cycling stability of the battery. , …”
Section: Introductionmentioning
confidence: 99%